Factors associated with Anemia among Orang Asli children aged two to six years in Negeri Sembilan, Malaysia - Murtaza, Siti Fatihah; Ling, Jun Lee; Usaini, Nur Nadhirah; Wan, Ying Gan; Sulaiman, Norhasmah (Springer Nature, 2023)
Background Anemia is a global public health problem that needs urgent attention, especially in early childhood. Young children living in remote indigenous communities are vulnerable to anemia. This study aimed to determine factors associated with anemia among children of the Orang Asli (OA) community, aged two to six years old.